The literary 100 [electronic resource] : a ranking of the most influential novelists, playwrights, and poets of all time - Burt, Daniel S. (Facts on File library of world literature, 2009)
Here is the revised and expanded edition of Daniel S. Burt's assessment of the 100 most influential novelists, playwrights, and poets of all times and cultures--now with 25 additional entries and some reassessments as well as 25 new black-and-white phot